ANALISA MITIGASI RISIKO MANAJEMEN RANTAI PASOKAN MENGGUNAKAN PENDEKATAN HOUSE OF RISK PADA PERUSAHAAN MANUFAKTUR TEPUNG AGAR-AGAR INSTAN - Dennis Marchello; Wilson Kosasih; Lithrone Laricha Salomon (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
Every company must have a good supply chain flow to support the company's development. A series of complex supply chain processes makes business processes unavoidable from risks that have a negative impact. Some risk events that are often found include the inability of suppliers to fulfill orders on the specified date, problems experienced by machines, and others. To overcome the risks that arise, it is necessary to manage supply chain risk management using the House of Risk (HOR) approach. The HOR method consists of 2 phases, HOR phase 1 focuses on risk events and priority handling of risk sources (risk agents) that will be subject to risk mitigation assistance measures to deal with negative pathways from these risks. While HOR phase 2 focuses on designing mitigation actions that will be applied to companies to deal with the negative impacts of risks and prevent risks from happening again. The results of the study showed that there were 47 risk events and 48 risk agents with 2 priority risk agents. Thus, 8 risk mitigation action strategies and 3 priority risk mitigation action strategies have been set to mitigate the existing risk agents.